Pengelolaan Sampah Daur Ulang Sebagai Kreasi Seni Masyarakat Doudo - Latifah Handayani; Setyo Yanuartuti (Universitas Negeri Medan, 2020)
Society can be called the human life that is in a single unit, interact with each other according to the prevailing custom system, is continuous, and is bound by shared identity. Doudo Village, until 2015, had a serious problem with household waste problems. The community as the party involved, is obliged to manage household rubbish as an effort to protect the environment. The method used in this study is a qualitative method by taking a case in Doudo Village. The purpose of this study is to explain the Doudo Village Community system which has two ways of managing their household waste. Namely, through the garbage bank, which is deposited once a week. Then also, how they process the results of the garbage bank into an art creation, which has a sale value. The results of this study can be seen from changes in local values in producing a creative economy. In the form of weekly income of residents who deposit waste at the Trash Bank. As well as artistic creations made from the results of garbage collection at the Trash Bank itself.